Mechanics of biomimetic free-standing lipid membranes: insights into the elasticity of complex lipid compositions - Griffo, Alessandra; Sparn, Carola; Lolicato, Fabio; Nolle, Friederike; Khangholi, Navid; Seemann, Ralf; Fleury, Jean-Baptiste; Brinkmann, Martin; Nickel, Walter; Hähl, Hendrik (RSC Advances, 2024)
The creation of free-standing lipid membranes has been so far of remarkable interest to investigate processes occurring in the cell membrane since its unsupported part enables studies in which it is important to maintain cell-like physicochemical properties of the lipid bilayer, that nonetheless depend on its molecular composition. In this study, we prepare pore-spanning membranes that mimic the composition of plasma membranes and perform force spectroscopy indentation measurements to unravel mechanistic insights depending on lipid composition. We show that this approach is highly effective for studying the mechanical properties of such membranes. Furthermore, we identify a direct influence of cholesterol and sphingomyelin on the elasticity of the bilayer and adhesion between the two leaflets. Eventually, we explore the possibilities of imaging in the unsupported membrane regions. For this purpose, we investigate the adsorption and movement of a peripheral protein, the fibroblast growth factor 2, on the complex membrane.
Online veröffentlicht: 22. April 2024
Gesehen am 11.09.2024